2006
DOI: 10.1037/0022-006x.74.5.841
|View full text |Cite
|
Sign up to set email alerts
|

Urban teens: Trauma, posttraumatic growth, and emotional distress among female adolescents.

Abstract: Urban teens face many traumas, with implications for potential growth and distress. This study examined traumatic events, posttraumatic growth, and emotional distress over 18 months among urban adolescent girls (N = 328). Objectives were to (a) describe types of traumatic events, (b) determine how type and timing of events relate to profiles of posttraumatic growth, and (c) prospectively examine effects of event type and posttraumatic growth on short- and long-term emotional distress with controls for pre-even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 75 publications
(78 reference statements)
7
100
2
Order By: Relevance
“…We contend that, as time passes, higher posttraumatic growth tends to be associated with a lower level of stress symptoms and vice versa. This contention seems to be supported by data showing that after controlling for baseline emotional stress, posttraumatic growth of adolescents was associated with subsequent reductions in long-term emotional distress (Ickovics et al 2006). Somewhat similar results were found among adults (Maguen et al 2006).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…We contend that, as time passes, higher posttraumatic growth tends to be associated with a lower level of stress symptoms and vice versa. This contention seems to be supported by data showing that after controlling for baseline emotional stress, posttraumatic growth of adolescents was associated with subsequent reductions in long-term emotional distress (Ickovics et al 2006). Somewhat similar results were found among adults (Maguen et al 2006).…”
Section: Introductionsupporting
confidence: 59%
“…It is manifested in better interpersonal relationships, an increased sense of personal strength, changed priorities, and a richer existential and spiritual life. Positive stress-related outcomes were reported in a large number of studies pertaining to posttraumatic growth (Hobfoll et al 2006a(Hobfoll et al , 2007aIckovics et al 2006;Weinrib et al 2006). This growth was expressed, for example, by an increase in pro-social behavior (Macksoud and Aber 1996), an enhanced sense of well-being (Bachar et al 1997) and heightened selfesteem (Baker 1990).…”
Section: Introductionmentioning
confidence: 94%
“…More recently, new emphasis has emerged, focusing on salutogenic factors, viewing crisis as a challenge with double potential: continuous pathology versus growth and readjustment. These favorable outcomes have been termed 'posttraumatic growth' (Hobfoll et al 2007;Hobfoll et al 2006;Ickovics et al 2006). A more modest and perhaps more realistic aim of posttraumatic growth is the ability of people to find "some good emerging from their struggle" (Tedeschi and Calhoun 1995, p. 445).…”
Section: Psychological Growth and Gendermentioning
confidence: 98%
“…28,40,49 These studies do not clarify whether posttraumatic stress precedes PTG or is a by-product of the process; PTG can also occur in the absence of posttraumatic stress. [20][21][22] The relation of depression and anxiety to PTG is less clear. Longitudinal studies have shown that both high and low levels of anxiety and low levels of depression correspond to PTG.…”
Section: Cognitive Processing Underlying Spi-ptgmentioning
confidence: 99%
“…[20][21][22] In order to account for a broader range of schema alteration we introduce the term ''threatened schemas'' to indicate the dynamic process through which schemas are changed in response to the traumatic event. The threat and resultant change can be conceptualized through two ends of a spectrum of schema alteration: (1) the traumatic event imparts change that is incorporated into preexisting schemas, with the threat essentially altered in meaning or interpretation and assimilated into an expanded worldview, or (2) the trauma overwhelms preexisting schemas, resulting in the creation or adoption of brand new schemas, composing a markedly reconfigured worldview.…”
Section: Ptg As Rebuilding or Reshaping The Worldviewmentioning
confidence: 99%